"These People Had Taken Advantage of Me": A Grounded Theory of Problematic Consequences of Player Interaction with Mobile Games Perceived as "Designed to Drive Spending". (28th August 2022) - Petrovskaya, Elena; Zendle, David
Abstract : Many games which incorporate microtransactions—uncapped, repeated in-game purchases—are described by players as having had their 'dynamics designed to drive spending'. Such games are perceived by players as designed primarily to encourage spending, rather than with the improvement of the player experience in mind. However, it is unknown how playing these games affects players. We addressed the research question of "What consequences might there be of interaction with games perceived as having had their dynamics designed to drive spending?" considering adult players. We conducted semi-structured interviews and used a grounded theory method of analysis. Our findings revealed five life areas of problematic consequences: financial issues, problems at work and education due to distraction and lack of productivity, emotional consequences for self-perception, problems sleeping, and social consequences. These outcomes emerge from the interaction of players with certain vulnerability traits with these game mechanics. We discuss these findings in the context of gaming disorder and the gamblification of games.